2012
DOI: 10.1155/2012/716235
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Fluid Analysis: Standstill or a Work in Progress?

Abstract: Pleural fluid analysis yields important diagnostic information in pleural effusions in combination with clinical history, examination, and radiology. For more than 30 years, the initial and most pragmatic step in this process is to determine whether the fluid is a transudate or an exudate. Light's criteria remain the most robust in separating the transudate-exudate classification which dictates further investigations or management. Recent studies have led to the evaluation and implementation of a number of add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 70 publications
(70 reference statements)
2
16
0
Order By: Relevance
“…6 High levels of ADA have also been reported in many other conditions including malignant effusion, rheumatoid arthritis, systemic lupus erythematosis, empyema and fungal infections. 1 In the present study two empyema cases of non tubercular origin showed very high values of ADA.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…6 High levels of ADA have also been reported in many other conditions including malignant effusion, rheumatoid arthritis, systemic lupus erythematosis, empyema and fungal infections. 1 In the present study two empyema cases of non tubercular origin showed very high values of ADA.…”
Section: Discussionsupporting
confidence: 57%
“…Accumulation of pleural fluid may be due to various causes such as increased pleural membrane permeability, increased capillary pressure, decreased oncotic pressure and lymphatic obstruction. 1 Transudative pleural effusions occur when systemic factors which effect the formation and absorption of pleural fluid are altered. Exudative pleural effusion occur secondary to local diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Various tests can be performed for pleural fluid (PF) analysis, either as sole or additional diagnostic tools to further determine the effusion’s etiology (4,5). …”
Section: Pleural Effusionsmentioning
confidence: 99%
“…Increased levels of NT-proBNP have been positively correlated with congestive heart failure as a cause of the PE (Porcel and Light 2006;Porcel 2013). Furthermore, CRP levels have been reported to be higher in parapneumonic PEs (Hassan et al 2012;Zou et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CRP levels have been reported to be higher in parapneumonic PEs (Hassan et al. ; Zou et al. ).…”
Section: Introductionmentioning
confidence: 99%